Telecommunications Services And Its Impact On Users - Kamaruddin, Kamaryati (2008)
This study analyses the possible significant impacts of mobile phone telecommunication services and determines whether the services does create changesin the users daily lives. The objective of the study was to develop and understanding that links mobile telecommunication services adoption, behavior patterns and competitive advantages that it brings into the environment.